Suicide ideation among oncologic patients in a Spanish ward. Issue 3 (2nd April 2016) - Diaz-Frutos, D.; Baca-Garcia, E.; Mahillo-Fernandez, I.; Garcia-Foncillas, J.; Lopez-Castroman, J.
Abstract : Oncologic patients are exposed to a higher risk of suicidal behaviors than the general population. In this study, we aim to examine the severity of suicidal ideation in a sample of oncologic patients considering different psychological and clinical features. We interviewed 202 inpatients receiving curative or palliative treatment in a medical oncology ward of a Spanish hospital during the period 2012–2014. A complete assessment of psychosocial factors, cancer diagnoses (lung, colon rectum, and genitourinary system), and suicidal behaviors were made during admission, including validated questionnaires about depression, anxiety, personality, quality of life, body image, life threatening events, hopelessness, and suicidal ideation. The characteristics of inpatients with high and low suicidal ideation were retrospectively compared. A logistic regression model was constructed to examine the relationship between the significant factors retained after the univariate analyses. One of every four patients ( n  = 51; 25.24%) presented high scores of suicidal ideation. Logistic regression analyses retained depression (OR = 3.55; 95% CI = 1.25–11.68; p  = .016), hopelessness (OR = 8.78; 95% CI = 3.44–25.88; p  ≤ .001), personality (OR = .44; 95% CI = .2–.96; p  = .038), and advanced age (OR = 2.60; 95% CI = 1.18–5.98; p  = .016) as the main risk factors for high suicidal ideation. Suicidal ideation was frequent among oncologic patients. These patients should receive closer monitoring, especially, when old, retired, or severely depressed.